2017
DOI: 10.2514/1.j055248
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for Acoustic Damping in a Helmholtz Solver

Abstract: Thermoacoustic Helmholtz solvers provide a cheap and efficient way of predicting combustion instabilities. However, because they rely on the inviscid Euler equations at zero Mach number, they cannot properly describe the regions where aerodynamics may interact with acoustic waves, in the vicinity of dilution holes and injectors, for example. A methodology is presented to incorporate the effect of non-purely acoustic mechanisms into a threedimensional thermoacoustic Helmholtz solver. The zones where these mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…This linear model accounts for acoustic propagation and the effects of sudden area changes but all dissipation mechanisms are neglected. However, it is known that an important source of acoustic damping within the flow comes from the coupling between vortical structures generated in shear layers and acoustic waves [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…This linear model accounts for acoustic propagation and the effects of sudden area changes but all dissipation mechanisms are neglected. However, it is known that an important source of acoustic damping within the flow comes from the coupling between vortical structures generated in shear layers and acoustic waves [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…An example of such a model is the ζ − l eff model [25,[55][56][57]. These types of acoustic loss models yield good results for swirling injectors [33,58], but they are linear. As a consequence, the predictions of the DATM coefficients according to these models do not depend on the forcing level and the nonlinearities observed in Fig.…”
Section: Cold Flow Operating Conditionsmentioning
confidence: 99%
“…Indeed, several studies deduced matrix coefficients for acoustically passive combustor parts of varying complexity, e.g., a single orifice [3], a tandem orifice [4], multiperforated liner plates [5], or a premixed nozzle [6]. The acoustic transfer behavior of swirl generators, which are an unavoidable part in swirl stabilized combustion systems, was numerically determined by Gikadi et al [7] and Ni et al [8]. A system of algebraic equations may be constructed from the collection of transfer (or scattering) matrices of the combustor elements.…”
Section: Transfer and Scattering Matricesmentioning
confidence: 99%
“…Experience has shown that this kind of analysis provides not only quantitative data on stability limits and dynamics of a combustion system but also important physical insight [9,[11][12][13][14][15][16]. Several previous studies have concentrated on the transfer or scattering matrices of individual combustor elements such as a flame, a burner, a swirl nozzle, or a dissipative element [3][4][5][6]8,9,11,13,14,[17][18][19]. The present study concerns in an integrated fashion a combustor scattering matrix that includes swirler, injection tube, and flame as well as parts of the combustion chamber, see Fig.…”
Section: Transfer and Scattering Matricesmentioning
confidence: 99%